<span>Y(−3, 4) is the original
</span><span>(x, y) → (x − 2, y + 1) is the rule you're using
(-3, 4) </span>→ (-3 - 2, 4 + 1)
(-3, 4) → (-5, 5)
<span>Y'(–5, 5)</span>
you have to make sure that they have the same denominator so
31/4 -4 2/4
= - 1 1/4
hope this helped you hon
First write the equation
3/n = 5
Multiply both sides by n
3/n * n = 5 * n
Simplify
3 = 5 * n
Divide both sides by 5
3/5 = 5 * n/5
Simplify
3/5 = n
Divide
0.6 = n
So 3/0.6 = 5
Given that ΔBDA is similar to ΔBDC and:
AD≡DC
AB≡BC
BD≡BD (shared side)
then the best postulate to use is the side-side-side (SSS) postulate.
Answer: SSS